Parameters of Chronic Kidney Disease to Identify Outpatients at Increased Risk for COVID-19 Mortality: A Cohort Study of UK Biobank Participants - Trivedi, Anusua; Liles, W. Conrad; Becker, Nicholas; Lavista Ferres, Juan M.; Lee, Dr. Aaron; Bhatraju, Dr. Pavan (The Open Urology & Nephrology Journal, 2021)
Coronavirus Disease (COVID-19) has resulted in a pandemic affecting more than a hundred countries worldwide [1]. Limited worldwide supply of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV) requires policymakers to prioritize high-risk populations for inoculation. Several clinical risk factors have been suggested to increase infection risk [2]. However, it is less well-known how pre-morbid, outpatient clinical variables influence COVID-19 risk of death. We retrospectively analyzed outpatient risk factors for death in the UK Biobank (UKBB), a large-scale prospective cohort comprising over 500,000 subjects aged 40-69 years recruited in 2006-2019 [3]. In this study, subjects with recorded mortality before 31st January 2020 (N = 28,930) were excluded since it was the date for the first recorded COVID-19 case in the UK. We performed a comprehensive study on primary care data and their associations with COVID-19 mortality in UKBB, controlling for possible confounding factors. To our knowledge, this is the broadest analysis of outpatient clinical factors and associations with COVID-19 to date.